Improvement of technical preparation of elite weightlifters by variation in the magnitude of training load - Oleshko Valentin; Ivanov Artem; Priimak Svetlana (National University of Physical Education and Sport of Ukraine, 2016)
Achievement of high sports performance by elite weightlifters depends on the technical and tactical actions performed during clean and jerk that are developed under the influence of various training loads. Athletes competed in middle-weight categories have the most efficient motor actions when perform clean and jerk. The largest number of technical errors of light-weight and middle-weight categories athletes are due to violations of the dynamic structure of a movement, whereas technical errors of weightlifters competed in heavy-weight categories are related to kinematic structure of a movement. The program of improvement of technical preparedness of elite weightlifters included the performance of series of compensatory exercises in different intensity zones, and this promotes an increased realization of the technical actions of athletes during performance of clean and jerk.